Enhancing a loosely coupled inductive wireless power transfer system for LED-driven slurry photocatalytic reactors - Zulkifly, Ab Aziz; Mohd Mawardi, Saari; Mohd Aufa Hadi Putera, Zaini; Nurul A'in, Nadzri; Chin, Sim Yee (Taylor and Francis Ltd., 2024)
To improve the irradiation profile in a conventional photocatalytic reactor, an LED-based light emitter energized by the inductive power transmission (IPT) method has been proposed recently. However, technical challenges such as low coupling due to the asymmetrical wireless coupler, dynamic impedance due to multiple receivers and changing magnetic properties in the transmitter core, and ease in upscaling remain to be addressed. This work proposes an IPT system for an LED-based photocatalytic reactor using a toroidal transformer to match the impedance between a modified Helmholtz transmitter coil and a class-E inverter. A finite element magnetic field simulation and analytical calculation of the induced voltage are used to assess the field uniformity inside the coil. The mutual inductance at selected locations within the coil volume and the power transfer efficiency (PTE) are evaluated. The proposed system requires less than 2 W to generate a uniform magnetic field inside a 10.6 L acrylic cylinder with an induced voltage of 13.9 ± 0.95 Vrms along the cylinder’s central axis. The proposed wireless coupler achieves a coupling coefficient of 0.013–0.034 and a PTE of 23.7%, outperforming similar systems with asymmetrical coupler design while offering a versatile solution for integrating IPT technology into wastewater treatment.